2017
DOI: 10.1097/ta.0000000000001330
|View full text |Cite
|
Sign up to set email alerts
|

Rib fracture fixation in the 65 years and older population

Abstract: Therapeutic/care management study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 10 publications
2
40
0
Order By: Relevance
“…Encouraged by favorable results with regard to ventilator days and risk of complications after surgical rib fixation in patients with flail chest as shown in the randomized trial by Marasco et al, some have advocated surgical rib fixation in the elderly patient with multiple (non flail chest) rib fractures too [13, 14]. A recent retrospective case control study by Fitzgerald et al supports this strategy; surgical rib fixation was associated with lower rates of pneumonia, respiratory readmissions in ICU and death [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Encouraged by favorable results with regard to ventilator days and risk of complications after surgical rib fixation in patients with flail chest as shown in the randomized trial by Marasco et al, some have advocated surgical rib fixation in the elderly patient with multiple (non flail chest) rib fractures too [13, 14]. A recent retrospective case control study by Fitzgerald et al supports this strategy; surgical rib fixation was associated with lower rates of pneumonia, respiratory readmissions in ICU and death [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…As only two studies, both retrospective cohort studies with small sample sizes and short follow-up, have singularly focused on operative versus nonoperative management of multiple simple rib fractures, definitive proof for the optimal treatment of multiple simple rib fractures is not achieved yet [9, 14, 3941].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the small sample size, this data did not reach statistical significance. It is worth noting that patient questionnaires in this study implied that rib plating was associated with decreased narcotic use, earlier absence of respiratory fatigue, and earlier lifestyle satisfaction achievement [43] . To our knowledge, there are currently 3 studies that examine long term outcomes and QOL in patients who have undergone SSRF.…”
Section: Implantsmentioning
confidence: 69%
“…In a review following rib plating versus non-operative management in patients age 65 and older, a patient population that has a well documented increased mortality rate at 20% and increased pneumonia rate at 19% [42] ; Fitzgerald et al found that those 50 patients treated non-operatively there were 4 respiratory related readmissions, 2 deaths, 7 cases of pneumonia, 7 pleural effusions, and 19 pneumothoraces compared with zero in the operatively managed group [43] . Again, the rib plating group had decreased ICU length of stay and accelerated rehabilitation compared with the injury matched control group despite having higher overall ISS scores.…”
Section: Implantsmentioning
confidence: 99%